The Impact of Teacher Experience and Motivation on the Performance of Elementary School Teachers in Wawo District, Bima, NTB - Patty, Elyakim Nova Supriyedi; Iriyani, Sri Astuti; Hadi, Heri Sopian; Marlina, Marlina; Ria, Reny Refitaningsih Peby (Jurnal Simki Pedagogia, 2024)
This research aims to explain the following: (1) The joint impact of experience and motivation on teacher performance. (2) the impact of teacher experience on teacher performance and (3) the impact of teacher motivation on teacher performance in Wawo sub-district, Bima, NTB. The sample for this research consisted of 153 certified civil servant educators from Wawo District, Bima Regency. The "random sampling" method was used to select 110 educators at random. Data collection in this study was obtained through tests and questionnaires. The reliability coefficient of teacher performance was rtt = 0.897, and the reliability coefficient of teacher motivation was rtt = 0.850, after giving the test instruments to 25 teachers outside the teacher sample took it. Teacher performance was 0.885 and principal leadership was 0.941. Descriptive quantitative analysis, multiple linear regression analysis, and partial correlation analysis were used to analyze the data in this research. The correctness of the data was checked with the help of computing software. The results of this research concluded that (1) teacher experience and teacher motivation have a positive and statistically significant effect on teacher performance. Effectively, 16.08% of teacher performance can be attributed to teacher motivation factors, followed by 11.45% of teacher experience factors; (2) the teacher experience factor has a significant positive effect on teacher performance. There is a positive correlation between teacher motivation and student achievement; (3) teacher performance increases with increasing years of experience. The more inspired a teacher is, the more effective they are in the classroom.